Analisis Pengendalian Kualitas dengan Metode Six Sigma Pada Produksi Packaging PT. ABC - Aldi, Muhammad Aldizan Wijaya; Nugraha, Asep Erik (Fakultas Teknik Universitas Tulang Bawang, 2024)
The development of industry in this current era is progressing rapidly, marked by increasing competition among companies. The method used is the Six Sigma method with the DMAIC approach (Define, Measure, Analyze, Improve, and Control). With this method, data obtained includes a total number of both good and defective products, which are then classified into several predefined defect categories by the company. Based on the data analysis results from July 2022 to December 2022, PT ABC identified four types of defects in packaging products. These defects include sticking with a defect percentage of 54%, cracking at 27%, coloring at 18%, and scratching at 2%. Improvement efforts can be made through training, guidance, and supervision of operators to enhance product quality. Additionally, strict supervision of raw materials in packaging production is necessary to ensure their quality is maintained. Furthermore, the machine setting process also requires supervision and guidance, with the implementation of clear Standard Operating Procedures (SOP) for each product. Keywords: DMAIC, Quality Control, Six Sigma